(untitled) (Economics and region, 2020)
The legal bases of realization of the state agrarian policy in Ukraine are investigated. The composition of the agrarian legislation of Ukraine is determined. The legislation of the European Union in the field of agriculture is analyzed. Agrarian relations are regulated by a wide range of bylaws, which contain general legal norms and do not define specific mechanisms for the functioning of the agricultural sector of the state economy. Legal norms governing the implementation of state agricultural policy should be defined at the level of law, which clearly sets out the principles of state implementation of measures aimed at intensive agricultural development, taking into account the priorities that correspond to the course of European integration. Adoption of the law will contribute to the creation of a unified legislative approach to the formation and implementation of state agricultural policy and state policy of rural development. It is substantiated that the implementation of the law will ensure the creation of favorable conditions for living in rural areas, sustainable economic growth of the agricultural food sector, the formation of a favorable investment climate in the agro-industrial complex and strengthening Ukraine’s export potential in agriculture.